Spinal Accessory Nerve Injury following Spinal Adjustment: Case Report and Literature Review of the Outcome of Accessory Nerve Pathology as Result of Blunt Trauma (Spinal Accessory Nerve Palsy after Spinal Adjustment) - Sulaiman Alanazi; Areej M. Alawfi; Bander S. Alrashedan; Reem A. Almohaini; Majed M. Shogair; Talal A. Alshehri (Case Reports in Orthopedics)
Spinal accessory nerve palsy (SANP) is rare and is commonly presented following iatrogenic injury. Their diagnosis is often missed on initial presentation. Injury following blunt trauma is rare, with few cases reported in literature describing blunt-associated SANP and their treatment and recovery. We present and discuss a case of SANP following an aggressive soft tissue adjustment by an uncertified individual that has been responsive to nonsurgical measures over 18 months. We also reviewed the related literature on similar cases that were presented as result of direct pressure on the nerve from soft tissue manipulation or heavy lifting and their outcome following treatment. Chiropractic is generally a safe complimentary medicine and must only be practiced by trained personnel. We found that blunt-caused SANP injuries should initially be treated conservatively as they are likely to respond and recover unlike when presented following invasive trauma accordingly to what we found in literature.